The SWIS trial: Protocol of a pragmatic cluster randomised controlled trial of school based social work - Westlake, D; Pallmann, P; Lugg-Widger, F; Forrester, D; Petrou, S; Daher, S; Adara, L; Cook, L; Munnery, K; Bennett, V; Smith, P; White, J (Public Library of Science, 2022)
Background Child and family social workers in the UK work closely with other agencies including schools and the police, and typically they are based in local authority offices. This study will evaluate the effectiveness of placing social workers in schools (SWIS) on the need for social care interventions. SWIS was piloted in three local authorities in 2018–2020, and findings from a feasibility study of the pilots suggests SWIS may operate through three key pathways: (1) by enhancing schools’ response to safeguarding issues, (2) through increased collaboration between social workers, school staff, and parents, and (3) by improving relationships between social workers and young people. Methods The study is a two-arm pragmatic cluster randomised controlled trial building on three feasibility studies which found SWIS to be promising. Social workers will work within secondary schools across local authorities in England. 280 mainstream secondary schools will be randomly allocated with a 1:1 ratio to SWIS or a comparison arm, which will be schools that continue as normal, without a social worker. The primary outcome will be the rate of Child Protection (Section 47) enquiries. Secondary outcomes will comprise rate of referrals to children’s social care, rate of Child in Need (Section 17) assessments, days spent in care, and educational attendance and attainment. The study also includes an economic evaluation, and an implementation and process evaluation. Social care outcomes will be measured in July 2022, and educational outcomes will be measured in July 2023. Days in care will be measured at both time points. Discussion Findings will explore the effectiveness and cost-effectiveness of SWIS on the need for social care interventions. A final report will be published in January 2024. Trial registration The study was registered retrospectively with the International Standard Randomised Controlled Trial Number registry on 13.11.2020 (ISRCTN90922032).